ARTIFICIAL INTELLIGENCE OF HIGHER ORDER THINKING IN SCIENCES EDUCATION: A BIBLIOMETRIC ANALYSIS - Haron, Azlina; Ishak, Nor Asniza; Othman, Siti Zuraidah Md (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This research demonstrates a bibliometric analysis of research on the integration of Artificial Intelligence (AI) in fostering Higher-Order Thinking (HOT) within science education, an area that has gained significant attention in the context of digital transformation in teaching and learning. Although AI has been widely applied across various disciplines, its role in enhancing critical thinking, problem-solving, and creativity in science education remains underexplored. This raises the need to map the intellectual structure, collaboration patterns, and research trends in this emerging field. Data were collected using the Scopus database through an advanced search strategy with the keywords “sciences,” “education,” “artificial intelligence,” and “higher order thinking,” yielding a final dataset of 2,009 publications. The data were cleaned and harmonized using OpenRefine, descriptive statistics and trend analyses were generated with the Scopus Analyzer, and visualization maps were constructed using VOSviewer. The results indicate a steady growth of publications, with a sharp increase from 2019 onward, reflecting the accelerated adoption of AI-driven pedagogical approaches. China, the United States, and the United Kingdom emerged as the most productive and highly collaborative countries, while leading keywords such as “artificial intelligence,” “students,” “machine learning,” and “higher education” demonstrated the thematic concentration of the field. Co-authorship and co-occurrence analyses further revealed eight distinct clusters, highlighting interdisciplinary collaborations that connect traditional science education with generative AI technologies. This study contributes to the body of knowledge by providing a systematic overview of how AI applications are shaping HOT in science education, identifying current research hotspots, and offering insights into potential directions for future pedagogical innovation and international collaboration.